Abrupt Bølling warming and ice saddle collapse contributions to the Meltwater Pulse 1a rapid sea level rise - Lauren J. Gregoire; Bette Otto‐Bliesner; Paul J. Valdes; Ruza Ivanovic (Geophysical Research Letters)
Abstract Elucidating the source(s) of Meltwater Pulse 1a, the largest rapid sea level rise caused by ice melt (14–18 m in less than 340 years, 14,600 years ago), is important for understanding mechanisms of rapid ice melt and the links with abrupt climate change. Here we quantify how much and by what mechanisms the North American ice sheet could have contributed to Meltwater Pulse 1a, by driving an ice sheet model with two transient climate simulations of the last 21,000 years. Ice sheet perturbed physics ensembles were run to account for model uncertainties, constraining ice extent and volume with reconstructions of 21,000 years ago to present. We determine that the North American ice sheet produced 3–4 m global mean sea level rise in 340 years due to the abrupt Bølling warming, but this response is amplified to 5–6 m when it triggers the ice sheet saddle collapse.